Wigner term generated by isovector p-n pairing - Bentley Ian; Frauendorf Stefan (EPJ Web of Conferences, 2013)
The linear term proportional to |N – Z| in the nuclear symmetry energy (Wigner energy) is obtained in a model that uses isovector pairing on single particle levels from a deformed potential combined with a T→2${\overrightarrow T ^2}$ interaction. The pairing correlations are calculated by numerical diagonalization of the pairing Hamiltonian acting on the six or seven levels nearest the N = Z Fermi surface. The experimental binding energies of nuclei with N ≈ Z are well reproduced. The Wigner energy emerges as a consequence of restoring isospin symmetry.